Development of Smart Safety System for Nuclear Reactor Application - Mohd Shah, Shahril; Mohd Arifin, Muhammad Aizat; Tan Kai Yong,; Shahrom, Abdul Ammar; Yusof, Khairul Huda; Amirrudin, Nurul ‘Ain; Md. Sapari, Norazliani; Minat, Mohd Sabri (Multidisciplinary Applied Research and Innovation, 2024)
Safety doors in a nuclear reactor play a vital role in containing radiation, controlling reactor operations, and preventing the release of radioactive materials into the environment. This paper introduces a safety door interlock system designed to minimize radiation and pressure leaks from the reactor hall. When the reactor hall’s pressure becomes negative, limit switches on the doors automatically close due to the natural pressure difference between the areas. These limit switches serve as input signals for an Arduino UNO, which, upon activation, triggers outdoor indicator lights to alert personnel that all doors are closed during reactor operation. The current reactor door uses a seal method where the door is only sealed to prevent radiation from leaking outside. Our proposed cost-effective safety interlock system utilizes Arduino UNO, door-attached limit switches, and outdoor indicator lights to ensure the safety of nuclear hall and environment. Additionally, a Wi-Fi module extends the system’s mobility for remote monitoring of the reactor and environmental conditions. This paper also introduces a radiation monitoring system for Cherenkov radiation, which only activates when the reactor hall achieves negative pressure, ensuring radiation containment. Data and warnings are transmitted via a Wi-Fi module to a user’s phone or PC through the Blynk app. As a result, a negative pressure safety system was achieved, which can monitor the Cherenkov radiation. In conclusion, the proposed safety interlock doors are effective to maintain the safety and integrity of a nuclear reactor.